Comparison Between The Performance of Parametric Active Contour Models - Alwan, F. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Snakes, or active contours, are used extensively in computer vision and image processing applications, particularly to locate object boundaries. In this research, for the segmentation of anatomical structures in medical images three approaches were implemented and compared like (original snake model, distance potential force model and Gradient Vector Flow (GVF) snake model). We used Computed Tomography image (CT) for our experiments. Our experiments show that original snake model has two problems; first is the limited capture range and the second is the poor convergence. Distance potential force model solved only the first problem of original snake and failed with second problem. Gradient Vector Flow (GVF snake) provides a good capture rang and a good convergence; therefore good results are obtained where GVF snake could successfully segment the anatomical structures from CT images.